STRATEGI KOMUNIKASI KIAI PESANTREN DARUL FALAH DALAM PERUBAHAN BUDAYA MERARIQ NYONGKOLAN - Arifin, Muhamad; Muadin, Akhmad; Salabi, Agus Salim (LENTERA, 2019)
The aim of this paper is to explain the strategy applied by the Kyai to transform the traditional marriage ceremony of Merariq/Nyongkolan among the sasak people of Lombok into becoming more shariâ€™a friendly tradition. The kiai's communication strategy in changing the tradition of merariq nyongkolan in Sasak Lombok tribal community are: First, kiai as the leader of Pesantren Darul Falah Mataram communicates with the community of Sasak Lombok by using preaching method, bilá¸¥ikmah (wise). Second, kiai foster the harmonious relations with internal public and also external public. The kiai utilizes the graduates of Darul Falah to convey the kiai's messages and missions to the community through the majlÄ«s taâ€™lÄ«m or pesantren, Madrasah Diniyah, muá¹£allÄ, and the mosques which is led by them. Third, the kiai uses non-verbal communication through a social approach to the community by attending to the celebration's routine such as 'aqÄ«qah, dibaâ€™an, marriage celebration, maulÄ«d an-nabiy, death, and other religious events its held in private homes or in mosques and muá¹£allÄ. Fourth, the kiai uses communication by using forms of threats to the community, especially the to the gradutes of Pesantren Darul Falah, who if they invite the kiai to the merariq nyongkolan event but still using kecimol music then the kyai will not be present in that event. But, when the community use Islamic music such as rebana, marawis, and with a series of activities those are not contrary to the shari'ah, the kiai will be happy to attend the invitation.Keywords: Communication strategy, cultural change, Merariq Nyongkolan